Antioxidant Capacity of Some Extracts from Aronia and Lonicera Fruits - Valentina Cristina Negru; Eliza Oprea; Claudia Nicola; Maria Marinescu; Claudia-Valentina Popa (Chemistry Proceedings, 2022)
Studies in the literature have shown high levels of phenolic compounds in the fruits of Aronia melanocarpa (fam [...]